Irregular meal pattern and later sleep midpoint are associated with increased BMI z-score and waist-height ratio during early adolescence - Sohvi Lommi; Sohvi Lommi; Elina Engberg; Elina Engberg; Aku-Ville Lehtimäki; Reetta Lehto; Reetta Lehto; Heli Viljakainen; Heli Viljakainen (Frontiers Media S.A., 2024)
BackgroundRapid gains in adiposity may have more adverse health implications in later life compared with having stable adiposity throughout childhood and adolescence. A knowledge gap concerns concomitant health behaviors contributing to adiposity gain among adolescents.ObjectivesWe investigated the associations of health behaviors relating to dietary habits, sleep, physical activity (PA), and screen time with an increase in body mass index z-score (BMIz) and waist-height ratio (WHtR) during adolescence.MethodsWe included 4,785 adolescents (53% of girls) aged 11.1 (SD 0.8) years at baseline and followed them for 3 years. We clustered them into decreased, stable, and increased BMIz and WHtR categories using the K-means clustering method. Using Cox regression, we computed hazard ratios (HR) with 95% CI for the associations of self-reported health behaviors (dietary habits, physical activity, sleep midpoint, and sedentary digital media use) with belonging to an increased BMIz or WHtR group. In a subsample (n = 3,840), we ran a sensitivity analysis considering puberty status as an additional covariate.ResultsLater sleep midpoint (having later midpoint of sleep between bedtime and waking time) and irregular meal pattern (not eating lunch and dinner every school day) predicted increased BMIz (HR 1.26 [95% CI 1.13-1.41] and 1.23 [1.08-1.39], respectively) and WHtR (1.23 [1.09-1.39] and 1.18 [1.02-1.36], respectively) over the follow-up period, after adjusting for other health behaviors. Associations remained after considering puberty status as a covariate.ConclusionsEarly bedtime with adequate sleep duration and regular meal pattern should be encouraged to prevent adiposity gain during early adolescence.